Neural Correlates of Levels of Emotional Awareness: Evidence of an Interaction between Emotion and Attention in the Anterior Cingulate Cortex - Lane, Richard D.; Reiman, Eric M.; Axelrod, Beatrice; Yun, Lang-Sheng; Holmes, Andrew; Schwartz, Gary E. (Journal of cognitive neuroscience, 1998)
Recent functional imaging studies have begun to identify the neural correlates of emotion in healthy volunteers. However, studies to date have not differentially addressed the brain areas associated with the perception, experience, or expression of emotion during emotional arousal. To explore the neural correlates of emotional experience, we used positron emission tomography (PET) and 15O-water to measure cerebral blood flow (CBF) in 12 healthy women during film- and recall-induced emotion and correlated CBF changes attributable to emotion with subjects' scores on the Levels of Emotional Awareness Scale (LEAS), a measure of individual differences in the capacity to experience emotion in a differentiated and complex way. A conjunction analysis revealed that the correla-tions between LEAS and CBF during film- and recall-induced emotion overlapped significantly ( = 3.74, < 0.001) in Brod-mann's area 24 of the anterior cingulate cortex (ACC). This finding suggests that individual differences in the ability to accurately detect emotional signals interoceptively or exteroceptively may at least in part be a function of the degree to which the ACC participates in the experiential processing and response to emotion cues. To the extent that this finding is consistent with the functions of the ACC involving attention and response selection, it suggests that this neural correlate of conscious emotional experience is not exclusive to emotion.